Exploring Benzo[ b ][1,4]Thiazine Derivatives: Multitarget Inhibition, Structure–Activity Relationship, Molecular Docking, and ADMET Analysis - Alishba; Ali, Irfan; Hameed, Shehryar; Khan, Khalid Mohammed; Salar, Uzma; Taha, Muhammad; Sadeghian, Nastaran; Taslimi, Parham; Tuzun, Burak; Özerkan, Dilşad; Dedeakayogullari, Huri; Ulukaya, Engin (Wiley, 2024)
Abstract A series of benzothiazine derivatives ( 1 – 17 ) were synthesized via an intermolecular cyclocondensation reaction involving 2‐aminothiophenol ( i ) and substituted phenacyl bromide ( ii ). Structural elucidation of these synthetic derivatives utilized EI–MS, HR‐EIMS, 1 H NMR, and 13 C NMR spectroscopic techniques. The synthesized analogs were evaluated against key enzyme targets (acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and α‐glucosidase (α‐Glu)) and tested for cytotoxicity against various cancer cell lines. Six compounds were selected based on their inhibition profiles, exhibiting significant inhibitory potential against enzymes. In silico studies corroborated the observed inhibitory activities, aligning closely with experimental outcomes. Additionally, an ADME/T study provided insights into pharmacokinetic and safety profiles, identifying promising candidates for future drug development efforts.
Keywords: Synthesis; Diabetes; Alzheimer's disease; Alzheimer's Disease; ADME/T; Adme/T; Cancer